Peach Fruit Development: A Comparative Proteomic Study Between Endocarp and Mesocarp at Very Early Stages Underpins the Main Differential Biochemical Processes Between These Tissues - Rodriguez, Carlos E.; Bustamante, Claudia A.; Budde, Claudio O.; Müller, Gabriela L.; Drincovich, María F.; Lara, María V. (Frontiers in Plant Science, 2019)
Peach (Prunus persica) is an important economically temperate fruit. The development follows double sigmoid curve with four phases (S1 to S4). We centered our work in the early development. In addition to S1, we studied the very early stage (E) characterized by the lag zone of the exponential growing phase S1, and the second stage (S2) when the pit starts hardening. “Dixiland” peach fruit were collected at 9 (E), 29 (S1), and 53 (S2) days after flowering and endocarp and mesocarp were separated. There was a pronounced decrease in total protein content along development in both tissues. Quantitative proteomic allowed the identification of changes in protein profiles across development and revealed the main biochemical pathways sustaining tissue differentiation. Protein metabolism was the category most represented among differentially proteins in all tissues and stages. The decrease in protein synthesis machinery observed during development would be responsible of the protein fall, rather than a proteolytic process; and reduced protein synthesis during early development would reroute cell resources to lignin biosynthesis. These changes were accompanied by net decrease in total amino acids in E1-S1 and increase in S1-S2 transitions. Amino acid profiling, showed Asn parallels this trend. Concerted changes in Asn and in enzymes involved in its metabolism reveal that increased synthesis and decreased catabolism of Asn may conduct to an Asn increase during very early development and that the β-Cyano-Alanine synthase/ β-Cyano-Alanine hydratase could be the pathway for Asn synthesis in “Dixiland” peach fruit. Additionally, photosynthetic machinery decays during early development in mesocarp and endocarp. Proteins related to photosynthesis are found to a higher extent in mesocarp than in endocarp. We conclude mesocarpic photosynthesis is possible to occur early on the development, first providing both carbon and reductive power and latter only reductive power. Together with proteomic, histological tests and anatomical analysis help to provide information about changes and differences in cells and cell-walls in both tissues. Collectively, this work represents the first approach in building protein databases during peach fruit development focusing on endocarp and mesocarp tissues and provides novel insights into the biology of peach fruit development preceding pit hardening.